Lymphotoxin-α is a novel adiponectin expression suppressor following myocardial ischemia/reperfusion - Lau, Wayne Bond (American Physiological Society, 2013)
Recent clinical observations demonstrate adiponectin (APN), an adipocytokine with potent cardioprotective actions, is significantly reduced following myocardial ischemia/reperfusion (MI/R). However, mechanisms responsible for MI/R-induced hypoadiponectinemia remain incompletely understood. Adult male mice were subjected to 30-min MI followed by varying reperfusion periods. Adipocyte APN mRNA and protein expression and plasma APN and TNFα concentrations were determined. APN expression/production began to decline 3 h after reperfusion (reaching nadir 12 h after reperfusion), returning to control levels 7 days after reperfusion. Plasma TNFα levels began to increase 1 h after reperfusion, peaking at 3 h and returning to control levels 24 h after reperfusion. TNFα knockout significantly increased plasma APN levels 12 h after reperfusion but failed to improve APN expression/production 72 h after reperfusion. In contrast, TNF receptor-1 (TNFR1) knockout significantly restored APN expression 12 and 72 h after reperfusion, suggesting that other TNFR1 binding cytokines contribute to MI/R-induced APN suppression. Among many cytokines increased after MI/R, lymphotoxin-α (LTα) was the only cytokine remaining elevated 24–72 h after reperfusion. LTα knockout did not augment APN levels 12 h post-reperfusion, but did so by 72 h. Finally, in vitro treatment of adipocytes with TNFα and LTα at concentrations seen in MI/R plasma additively inhibited APN expression/production in TNFR1-dependent fashion. Our study demonstrates for the first time that LTα is a novel suppressor of APN expression and contributes to the sustained hypoadiponectinemia following MI/R. Combining anti-TNFα with anti-LTα strategies may achieve the best effects restoring APN in MI/R patients.